Influence of irradiation parameters on the polymerization of ceramic reactive suspensions for stereolithography. Issue 15 (December 2017) - Chartier, Thierry; Dupas, Cyrielle; Geffroy, Pierre-Marie; Pateloup, Vincent; Colas, Maggy; Cornette, Julie; Guillemet-Fritsch, Sophie
Abstract: Stereolithography is an additive manufacturing process which makes it possible to fabricate useful complex 3D ceramic parts, with a high dimensional resolution and a good surface finish. Stereolithography is based on the selective UV polymerization of a reactive system consisting in a dispersion of ceramic particles in a curable monomer/oligomer resin. In order to reach a homogeneous polymerization in the green part, and to limit the risk of cracking and/or deformation during subsequent stages of debinding and sintering due to internal stresses, the influence of various fabrication parameters (laser power, scanning speed, number of irradiations) on the degree of polymerization was investigated. In addition, the impact of the irradiation of the subsequent upper layers onto the previously deposited and irradiated layers was evaluated. The degree of conversion was determined by Fourier Transform Infrared Spectroscopy (FTIR). Raman spectroscopy was also used and a brief comparison between these two methods is given.